Pengaruh Lingkungan Terhadap Gaya Belajar Siswa pada Mata Pelajaran Bahasa Inggris di Kec. Koto Xi Tarusan, Pesisir Selatan - Lili Perpisa; Herviani Sevrika (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
The aim of this research is to describe the effect of environment toward studentsâ learning style in studying English at Kecamatan Koto XI Tarusan, Pesisir Selatan. English is an important subject for students since it has many tourism destinations. So, the students should have a capability in English in order to promote their areas. In learning English, each student has different way or different learning style. One of the factors that influences their learning style is an environment. The method of this reseach is causal-comparative. The sample used purposive sampling. The researcher chose 4 schools located in different environment; they are Junior High School number 9Â  located close to beach, Junior high SchoolÂ  number 1Â  located close to market, Senior High School number 2Â  located in hilly environment, and Senior High School number 1 located between hill and beach. The total of sample is 216 students and 216 studentsâ parents. The data were taken by using observation, questioneer and interview. The result of this research is the environment does not affect the students learning style in studying English since most of the students in 3 areas use common sense.